Absence of relationship between tuberculin reactivity and atopy in BCG vaccinated young adults. Issue 6 (1st June 2000) - Omenaas, E; Jentoft, H F; Vollmer, W M; Buist, A S; Gulsvik, A
Abstract : BACKGROUND: An inverse association between tuberculin responses and atopy has been observed in Japanese children, indicating that BCG immunisation, subclinical exposure to Mycobacterium tuberculosis without clinical disease, or host characteristics may influence the T helper (Th) lymphocyte balance with decreased atopy as a result. This study was undertaken to determine whether tuberculin reactivity is inversely related to atopy in young adults vaccinated with BCG at the age of 14. METHODS: Men and women aged 20–44 years were tested using the adrenaline-Pirquet test with Norwegian produced synthetic medium tuberculin (n = 891). In addition, their serum total and specific IgE antibodies against mite, cat, timothy grass, mould and birch were measured. RESULTS: Of the 574 subjects with complete examinations, 64% had a positive adrenaline-Pirquet tuberculin test (⩾4 mm) and 27% exhibited IgE antibodies (⩾0.35 kU/l) to one or more of the five specific allergens. The geometric mean of total serum IgE in the population was 30.2 kU/l. Tuberculin reactivity and log IgE were not correlated ( r = 0.043, p = 0.30). The mean tuberculin reactivity was 4.6 mm, 4.9 mm, and 5.0 mm in the lower, middle and upper tertile of IgE distribution (<14 kU/l, 14–61 kU/l, >61 kU/l). The prevalence of atopy, as assessed by either the presence of any of the five specific IgE antibodies or by each specific IgE antibody separately, did not differ between subjects with a positive and those with a negative tuberculin test. These results persisted after adjustment for age, sex, and smoking status in multivariate logistic regression analyses. CONCLUSIONS: In this young adult population, BCG vaccinated at the age of 14, no significant relationship between a positive tuberculin reaction and atopy was observed. If a true relationship had been found, our study suggests that it may be limited to populations immunised in early childhood when a substantial modulation of the immune system can occur.